Comparison of the management and in‐hospital outcomes of acute coronary syndrome patients in Australia and New Zealand: results from the binational SNAPSHOT acute coronary syndrome 2012 audit. Issue 5 (May 2015) - Ellis, C.; Hammett, C.; Ranasinghe, I.; French, J.; Briffa, T.; Devlin, G.; Elliott, J.; Lefkovitz, J.; Aliprandi‐Costa, B.; Astley, C.; Redfern, J.; Howell, T.; et al.
Abstract Background/Aims We aimed to assess differences in patient management, and outcomes, of Australian and New Zealand patients admitted with a suspected or confirmed acute coronary syndrome (ACS). Methods We used comprehensive data from the binational Australia and New Zealand ACS 'SNAPSHOT' audit, acquired on individual patients admitted between 00.00 h on 14 May 2012 to 24.00 h on 27 May 2012. Results There were 4387 patient admissions, 3381 (77%) in Australia and 1006 (23%) in New Zealand; Australian patients were slightly younger (67 vs 69 years, P = 0.0044). Of the 2356 patients with confirmed ACS, Australian patients were at a lower cardiovascular risk with a lower median Global Registry Acute Coronary Events score (147 vs 154 P = 0.0008), but as likely to receive an invasive coronary angiogram (58% vs 54%, P = 0.082), or revascularisation with percutaneous coronary intervention (32% vs 31%, P = 0.92) or coronary artery bypass graft surgery (7.0% vs 5.6%, P = 0.32). Of the 1937 non‐segment elevation myocardial infarction/unstable angina pectoris (NSTEMI/UAP) patients, Australian patients had a shorter time to angiography (46 h vs 67 h, P < 0.0001). However, at discharge, Australian NSTEMI/UAP survivors were less likely to receive aspirin (84% vs 89%, P = 0.0079, a second anti‐platelet agent (57% vs 63%, P = 0.050) or a beta blocker (67% vs 77%, P = 0.0002). In‐hospital death rates were not different (2.7% vs 3.2%, P = 0.55) between Australia and New Zealand. Conclusions Overall more similarities were seen, than differences, in the management of suspected or confirmed ACS patients between Australia and New Zealand. However, in several management areas, both countries could improve the service delivery to this high‐risk patient group.